تأثير موعد الإصابة بفيروس البطاطا واي (PVY) في إنتاجية صنفي التبغ برلي (Br21) وفرجينيا (Vk51) في الساحل السوري - اسماعيل عماد; محمد رامز; عباس نورا (Latakia University Journal -Biological Sciences Series, 2018)
هدف البحث إلى دراسة تأثير موعد العدوى بفيروس البطاطا واي (PVY) في إنتاجية صنفي التبغ برلي (Br21) وفيرجينيا (Vk51) في الساحل السوري. أُعديت نباتات التبغ بالطريقة الميكانيكية بعزلة محلية للفيروس, وقد اختلفت أعراض الإصابة الظاهرية وموعد تكشفها حسب صنف التبغ المدروس واختلاف موعد العدوى, وظهرت على الأوراق المعداة بالفيروس في الصنف برلي أعراضٌ موضعية, كما أدّت الإصابة إلى فقد في إنتاج صنفي التبغ برلي وفيرجينيا من الأوراق الخضراء وبالتالي المجففة, وازدادت نسبة الفقد في الإنتاج في الإصابة المبكرة مقارنة مع الإصابة المتأخرة. كما أثرت الإصابة بالفيروس إيجابياً في نسبة التصافي لصنفي التبغ برلي وفيرجينيا حسب موعد العدوى والصنفين المدروسين. This research was aimed to study the effect of Potato Y potyvirus (PVY) on the production of tobacco varieties White Burley (Br21) and Virginia (Vk51) in the Syrian coast. External symptoms caused by PVY, and its time of appearance, were variable according to the studied tobacco varieties and to the time of infection. Inoculated leaves of White Burley showed symptoms of local infection. The infestation of White Burley and Virginia plants with PVY led to yield losses of fresh tobacco leaves and subsequently on cured leaves; and yield losses were increased in the early infection in comparison with late infection. The infestation of tobacco varieties White Burley and Virginia with PVY significantly increased the net rate according to the time of infection and to the studied varieties.